(untitled) - Fellmann, Jerome Donald (New York, 1999)
The book is organized with five parts. Part I presents concepts and models of spacial interaction and spatial behavior and completes with a consideration of population structures, patterns and change. Part II through IV examines the landscapes of culture and organization resulting from human occupance of the earth and from spatial similarities and differences that occupation has engendered. These include cultural patterns of linguistic, religious, ethnic, folk, and popular geographic differentiation of peoples and societies and those of economic, urban, and political organization space. Part V draws together in sharper focus selected aspects of the human-environmental interface, of the human impact on the natural lanscape.
Keywords: Human geography